2015
DOI: 10.1038/srep14991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cellular microRNA-136 as a dual regulator of RIG-I-mediated innate immunity that antagonizes H5N1 IAV replication in A549 cells

Abstract: H5N1 influenza A virus (IAV) causes severe respiratory diseases and high mortality rates in animals and humans. MicroRNAs are being increasingly studied to evaluate their potential as therapeutic entities to combat viral infection. However, mechanistic studies delineating the roles of microRNAs in regulating host-H5N1 virus interactions remain scarce. Here, we performed microRNA microarray analysis using A549 human lung epithelial cells infected with a highly pathogenic avian influenza virus. The microRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 48 publications
(55 reference statements)
4
56
1
Order By: Relevance
“…Moreover, we observed only induction using the less sensitive approach of proteomic analysis. Some reports have indicated that certain transfected miRNAs can induce RIG-I (DDX58) gene expression in epithelial or mesenchymal stem cells, and trigger an antiviral response via specific TLR5 stimulation [67,68]. However, neither DDX58 nor TLR5 expression was induced by miR-182 transfection in this study, making this mechanism unlikely.…”
Section: Discussioncontrasting
confidence: 64%
“…Moreover, we observed only induction using the less sensitive approach of proteomic analysis. Some reports have indicated that certain transfected miRNAs can induce RIG-I (DDX58) gene expression in epithelial or mesenchymal stem cells, and trigger an antiviral response via specific TLR5 stimulation [67,68]. However, neither DDX58 nor TLR5 expression was induced by miR-182 transfection in this study, making this mechanism unlikely.…”
Section: Discussioncontrasting
confidence: 64%
“…Concomitantly, non-coding cellular Y-rNAs were found to accumulate in their 5′-PPP-containing form and to bind to RIG-I in HIV-1-infected cells 59 . Moreover, endogenous RNAs lacking the canonical features of RIG-I agonists, including RNAs cleaved by RNase L 60 and microrNAs (miRNAs) 61 , have been suggested to activate RIG-I in virus-infected cells. Finally, endogenous retroviral elements were shown to activate RIG-I via de-SUMOylation of the host transcriptional repressor tripartite motif-containing 28 (TRIM28; also known as KAP1) 62 .…”
Section: Rig-imentioning
confidence: 99%
“…Reports have demonstrated that miR-136 interacts at the post-translational level with RIG-I to increase proinflammatory cytokine production [21]. miRNAs, such as let-7, may also act directly on the mRNA of a pro-inflammatory cytokine, such as IL6, to prevent its translation [22].…”
Section: The Role Of Mirnas In the Innate Anti-viral Responsementioning
confidence: 99%